Boosting the efficiency of urea synthesis via cooperative electroreduction of N2 and CO2 on MoP. Issue 1 (30th November 2022) - Jiao, Dongxu; Dong, Yilong; Cui, Xiaoqiang; Cai, Qinghai; Cabrera, Carlos R.; Zhao, Jingxiang; Chen, Zhongfang
Abstract : By combining theoretical and experimental efforts, we designed the MoP-(101) surface and explored its potential as catalyst for urea production. Abstract : By combining theoretical and experimental efforts, we designed the MoP-(101) surface and explored its potential as catalyst for urea production. Our computations revealed that N2 and CO2 reactants can be effectively reduced to urea on the MoP-(101) surface with a low limiting potential (−0.27 V); the competitive side reactions are well suppressed, and the *NHCONH species is a key reaction intermediate for the C–N coupling during urea synthesis. Our experimental measurements confirmed the above theoretical predictions: urea synthesis was achieved with the urea formation rate of 12.4 μg h −1 mg −1 and the faradaic efficiency of 36.5%. This work not only highlights the critical role of the abundant Mo active sites for urea electrosynthesis but also provides a new mechanism for C–N coupling, which may be used to further develop other efficient electrocatalysts.